Arachnid monophyly: Morphological, palaeontological and molecular support for a single terrestrialization within Chelicerata. (November 2020) - Howard, Richard J.; Puttick, Mark N.; Edgecombe, Gregory D.; Lozano-Fernandez, Jesus
Abstract: The majority of extant arachnids are terrestrial, but other chelicerates are generally aquatic, including horseshoe crabs, sea spiders, and the extinct eurypterids. It is necessary to determine whether arachnids are exclusively descended from a single common ancestor (monophyly), because only that relationship is compatible with one land colonisation in chelicerate evolutionary history. Some studies have cast doubt on arachnid monophyly and recast the origins of their terrestrialization. These include some phylogenomic analyses placing horseshoe crabs within Arachnida, and from aquatic Palaeozoic stem-group scorpions. Here, we evaluate the possibility of arachnid monophyly by considering morphology, fossils and molecules holistically. We argue arachnid monophyly obviates the need to posit reacquisition/retention of aquatic characters such as gnathobasic feeding and book gills without trabeculae from terrestrial ancestors in horseshoe crabs, and that the scorpion total-group contains few aquatic taxa. We built a matrix composed of 200 slowly-evolving genes and re-analysed two published molecular datasets. We retrieved arachnid monophyly where other studies did not - highlighting the difficulty of resolving chelicerate relationships from current molecular data. As such, we consider arachnid monophyly the best-supported hypothesis. Finally, we inferred that arachnids terrestrialized during the Cambrian–Ordovician using the slow-evolving molecular matrix, in agreement with recent analyses. Highlights: Arachnids are ancestrally terrestrial or amphibious, and probably lacked gnathobasic feeding, compound eyes and book gills. It is unlikely that scorpions originated in aquatic environments. A highly complete molecular matrix of 200 slowly evolving genes with diverse taxon sampling yields Arachnida without model-dependency. Arachnids colonised land and diversified in the Cambrian–Ordovician.